KADAR HEMOGLOBIN LANSIA SETELAH KONSUMSI SERBUK DAUN KELOR (MORINGA OLEIFERA) - Supriyadi, Supriyadi; Dewi, Novita; Maemunah, Neni (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
ABSTRACT Iron deficiency is a problem that often occurs in the elderly as a result of the aging process. The use of Moringa oleifera leaf to occupy the need of nutritious meal which highly in vitamin and mineral especially iron was scarce. This research aim was to determine the influence of Moringa oleifera leaf powder on hemoglobin levels in the elderly. The pre-experimental research design was used to the sample of 16 respondents which were selected by consecutive sampling technique. The result showed the majority of the respondent were female within average of 65 years old. The paired T-test analysis obtained the hemoglobin levels was 13.76 g/dL (before Moringa oleifera leaf powder consumed) and increase after consumption to 15.13 g/dL (p-value of 0.031 0.05). It indicates there is an influence of Moringa oleifera leaf powder on hemoglobin levels in the elderly. It is recommended to further study the effect of Moringa oleifera leaf powder on the blood chemistry and SpO2 levels among the elder population. Keywords : Elderly, Hemoglobin, Moringa oleifera leaf powder ABSTRAK Defisiensi zat besi merupakan masalah yang sering terjadi pada seorang lansia akibat dari proses penuaan, untuk membantu memenuhi kebutuhan zat besi pada lansia maka dibutuhkan makanan yang kaya nutrisi dan mineral diantaranya daun kelor (moringa oleifera). Tujuan penelitian untuk mengetahui pengaruh serbuk daun kelor (moringa oleifera) terhadap kadar hemoglobin pada lansia. Desain penelitian ialah pre – eksperimen, dengan sampel 16 responden dipilih menggunakan tekhnik consecutive sampling. Hasil penelitian menunjukkan hampir seluruhnya berjenis kelamin perempuan sebanyak 13 responden (81.2%) dengan rerata usia responden ialah 65 tahun. Uji paired T-test didapatkan nilai rerata kadar hemoglobin sebelum konsumsi serbuk daun kelor yaitu 13.76 g/dL dan mengalami peningkatan sesudah konsumsi serbuk daun kelor yaitu 15.13 g/dL, dengan p value 0.031 dimana p value 0.05 berarti bahwa ada pengaruh konsumsi serbuk daun kelor (moringa oleifera) terhadap kadar hemoglobin. Peneliti selanjutnya dapat meneliti efektivitas serbuk daun kelor (moringa oleifera) terhadap kimia darah serta kadar SpO2 lansia. Kata kunci : Hemoglobin, Lansia, Serbuk daun kelor